Parental Leave and Intimate Partner Violence - Dan Anderberg; Line Hjorth Andersen; N. Meltem Daysal; Mette Ejrnæs (Institute of Labor Economics (IZA), 2025)
We examine the impact of a 2002 Danish parental leave reform on intimate partner violence (IPV) using administrative data on assault-related hospital contacts. Using a regression discontinuity design, we show that extending fully paid leave increased mothers' leave-taking and substantially reduced IPV, with effects concentrated among less-educated women. The reform also lengthened birth spacing, while separations remained unchanged and earnings effects were modest. The timing and heterogeneity of impacts point to fertility adjustments—rather than exit options or financial relief—as the key mechanism. Parental leave policy thus emerges as an underexplored lever for reducing IPV.
Keywords: J12; I38; 330; intimate partner violence; parental leave